A g-type lysozyme from the scallop Argopecten purpuratus participates in the immune response and in the stability of the hemolymph microbiota. Issue 123 (April 2022) - González, Roxana; González, Daniel; Stambuk, Felipe; Ramírez, Felipe; Guzmán, Fanny; Mercado, Luis; Rojas, Rodrigo; Henríquez, Carlos; Brokordt, Katherina; Schmitt, Paulina
Abstract: Lysozymes are antimicrobial acid hydrolases widely distributed in nature. They are located inside the cells in lysosomes, or they are secreted to the extracellular space, where they can lyse the cell wall of certain species of bacteria via hydrolysis of the peptidoglycan. Thus, lysozymes are bacteriolytic enzymes and play a major biological role in biodefense, as these enzymes can act as antibacterial and immune-modulating agents. In this study, we characterized a g-type lysozyme from the scallop Argopecten purpuratus named Ap Glys. The cDNA sequence comprises an open reading frame (ORF) of 600 nucleotides, codifying for a putative protein of 200 amino acids with a signal peptide of 18 amino acids. The deduced mature protein sequence displays a molecular weight of 20.07 kDa and an isoelectric point (pI) of 6.49. Ap Glys deduced protein sequence exhibits conserved residues associated with catalytic activity and substrate fixation in other g-type lysozymes. The phylogenetic analysis revealed a high degree of identity of Ap Glys with other mollusk g-type lysozymes, which form a restricted and separated clade from the vertebrate lysozymes. ApGlys transcripts were constitutively and highly expressed in the digestive gland, and it was induced in hemocytes and gills of scallops after an immune challenge. Furthermore, the Ap Glys protein was located inside hemocytes of immunostimulated scallops, determined by immunofluorescence analysis. Finally, the transcript silencing of Ap Glys by RNA interference led to an increase of total culturable bacteria from the scallop hemolymph. Furthermore, we detected a higher diversity of the bacterial community in Ap Glys-silenced scallops and an imbalance of certain bacterial groups present in the hemolymph by 16S rDNA deep amplicon sequencing. Overall, our results showed that Ap Glys is a new member of scallop lysozymes that is implicated in the immune response and in the microbial homeostasis of A. purpuratus hemolymph. Highlights: A g-type lysozyme was identified from the scallop hemocytes, named ApGlys. ApGlys transcripts were constitutively and highly expressed in the digestive gland. Ap Glys expression is upregulated in hemocytes and gills after immune challenge. Transcript silencing of Ap Glys by RNAi led to an imbalance of bacterial groups. Ap Glys is implicated in the bacterial homeostasis of A. purpuratus hemolymph.